Hubungan Pendidikan Formal Dengan Perilaku Pemeriksaan Tuberkulosis Keluarga Kontak Di Kabupaten Pamekasan - Ahmadi Ahmadi (Fakultas Ilmu Kesehatan, 2018)
Tuberculosis is a global problem and until now. In Indonesia tuberculosis became thenumber one killer among infectious diseases in the other. The disease caused by theMycobacterium tuberculosis germ is easily transmitted, due out the entry of germs from the bodyonly through the air. The study is quantitative using analitic approach of cross sectional.Research method with cross sectional approach (cut the latitude) is done at 379 samplesusing the technique of sampling groups two levels (two-stage cluster sampling).The results of the statistical test of Pearson Chi Square p = 0000 value obtained is smallerthan α = 0.05, so that there is a meaningful relationship between inferred levels of education withexamination of the behavior of tuberculosis in Pamekasan.